Greece : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2006)
This 2005 Article IV Consultation highlights that economic growth in Greece has been strong for several years, underpinned by a large fall in interest rates owing to adoption of the euro and subsequent European Central Bank easing. In 2005, the authorities implemented substantial fiscal consolidation, reducing the budget deficit to 4.6 percent of GDP on IMF staff calculations. Economic growth in 2006 and beyond is likely to be moderate compared with the high rates enjoyed in previous years, though it should remain comfortably above the euro area average.